Developing a Shared Understanding of Assessment Criteria and Standards for Undergraduate Mathematics : Final Report. - Varsavsky, Cristina; King, Deborah; Coady, Carmel; Hogeboom, Karen (Office for Learning and Teaching, 2014)
Final report from a project that engaged the mathematics community in a conversation around assessment standards which builds upon the Learning and Teaching Academic Standards project outcomes for science, and their contextualisation within the mathematics discipline. The authors aimed to influence assessment practices in mathematics departments, to move away from idiosyncratic marking and grading approaches that favour procedural mastery towards practices that measure the quality of all aspects of student work against external anchors ensuring comparability of standards within and across mathematics departments. The project resulted in agreed definitions of mathematics assessment criteria and standards expressed in terms of rubrics, and exemplars that demonstrate how judgements are made in the marking process. Together, these provide a reference framework and toolkit to support tertiary educators in the development of quality assessment standards and criteria.